Repeated Sprint Training in Hypoxia: Case Report of Performance Benefits in a Professional Cyclist - Faiss, Raphael; Rapillard, Arnaud (Frontiers in Sports and Active Living, 2020)
Repeated sprint training in hypoxia (RSH) has gained unprecedented popularity among the various strategies using hypoxia as an additional stimulus to improve performance. This case study reports the benefits of 150 repeated sprints in normobaric hypoxia over 10 days in a professional cyclist. After 3 weeks of endurance training in November, the cyclist performed 5 RSH sessions at a simulated altitude of 3300 m on his own bicycle attached to an indoor trainer in a hypoxic chamber (FiO2 14.1 ± 0.1 %, PiO2 94.6 ± 1.4 mm Hg). Each session consisted of 4 blocks of 7 all-out sprints of 6 s interspersed with 14 s active recovery (for a total of 126 s per block). After 12 min of warm-up with a single isolated 6 s reference sprint, the sessions included a first and a second sprinting block with 4 min 54 s active recovery in-between. After 9 min 54 s active recovery including an isolated 6 s reference sprint, a third and a fourth block were performed with 4 min 54 s active recovery in-between, before an active cool-down of 9 min 54 s. The total duration was thus of 50 min per session for a total hypoxic exposure of 250 min exercising. Power output and heart rate were monitored at 1Hz. Lactate concentration ([La]) and pulse oxygen saturation (SpO2) were measured at the start and end of each block during the first and fifth training session. Basal SpO2 was of 83% during session 1 and 85.5% during session 5. When comparing the first and fifth training session, peak power increased for the best 1 s value (+8%) and the best 5 s average (+10%) to reach 1041 W and 961 W, respectively. Average power for all blocks (including active recoveries) increased from 334 W to 354 W with a similar average heart rate during the sessions (146 ‘.min-1). Peak [La] was increased from 12.3 to 13.8 mmol.l-1. In conclusion, this case report illustrates a 10-days RSH intervention perceived as efficient in a professional cyclist and shown to improve total work (6-s sprints) produced for a similar physiological strain.